PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DIAWALI DENGAN BRAIN GYM (SENAM OTAK) DALAM PEMBELAJARAN MATEMATIKA - via, Ilta (FKIP UMSB, 2017)
Low student learning outcomes are caused by various factors, including the majority of students are less focused and less active during pembelajaan process, which makes difficult students to master the material so that students are lazy for homework given. One effort that can be done is to give teachers some Brain Gym movements (brain exercise) before the learning begins in order to focus more students during the learning process. The hypothesis put forward is the results of students 'mathematics learning that uses the Cooperative Learning Model Numbered Heads Together (NHT) Beginning with the Brain Gym (gymnastics of the brain) in Mathematics Learning is better than the results of students' mathematics learning without the use of Cooperative Learning Model Numbered Heads Together (NHT ) Beginning with brain Gym (gymnastics of the brain) in Mathematics Learning in class VIII SMP N 1 Batipuh.Penelitian done in class VIII SMP N 1 Batipuh. The results of study were taken in this study is the result of learning mathematics in the cognitive, affective and psychomotor. The instrument used was a test result of learning and observation sheet.Analysis of the final test result data by using t-test at 95% confidence level (Î± = 0.05) and 37 degrees of freedom is obtained t_hitung = 2,73> 1,68 = t _ ((0.95; 37)). which means H_0ditolak and H_1 received thus results of mathematics learning by applying Cooperative Learning Model Numbered Heads Together (NHT) Beginning with the Brain Gym (brain exercise) is better than the result of learning mathematics students who do not apply Cooperative Learning Model Numbered Heads Together ( NHT) Beginning with brain Gym (gymnastics of the brain) in Mathematics Learning in Class VIII SMP N 1 Batipuh.Â Keywords: Numbered HeadsTogether, Brain Gym